Aksi Hijau di Ujung Negeri Gerakan Bersih Sungai Bersama Warga - Rahayu, Kinari; Sumrahadi, Sumrahadi (Journal of Community Development and Empowerment, 2025)
Community-based environmental activities that directly involve residents are increasingly important for maintaining ecosystem sustainability, especially in remote or “edge-of-the-nation” areas that often have limited access to large government programs. The title “Green Action at the Nation’s Edge: A River Clean-Up Movement with Local Residents” describes a participatory initiative that engages local communities in cleaning river streams, restoring water quality, and raising ecological awareness in peripheral regions. Through mutual cooperation (gotong royong) and collaboration among residents, this movement aims not only to remove the physical burden of waste from the river but also to shift mindsets so that rivers are viewed as sources of life rather than dumping grounds. A series of activities—such as riverbank sweeping, collecting plastic and organic waste, and community education—are carried out together with various local stakeholders. The results of this movement show positive impacts, including increased citizen participation, the formation of environmentally concerned networks, a cleaner river, and strengthened social cohesion. This study also outlines several challenges, such as limited equipment, resistance to changing long-standing habits, and the need to maintain the movement’s sustainability after the initial action. In conclusion, the community-driven river clean-up movement at the nation’s edge demonstrates that small changes involving active community participation can generate significant ecological and social impacts. Further development should focus on strategies for continuous community engagement, water quality monitoring, and integrating local programs so that the movement becomes part of a broader environmental management system.